Discovering Millennials’ Migration Clusters in Seoul, South Korea: A Local Spatial Network Autocorrelation Approach - Youngbin Lee (Findings Press, 2021)
The spatial directionality of Millennials' migration has been underexplored. This study utilizes local spatial network autocorrelation to identify migration clusters of Millennials in a metropolitan area. The result found that Millennials migrate within an urban core and move to newer districts in surrounding areas. We found spatially distinct migration clusters by age group, possibly reflecting different motives through life stages. The analysis demonstrated that this method is effective for detecting migration clusters and for comparing subsets.